Innovative partnership scheme unlocks US$520,800 credit, boosting hundreds of Kenyan farmers’ resilience - Wamicwe, Peter; Derenoncourt, Marie Ena; Newman, Richard (2025)
During a financial product launch, a pre-approved credit line of US$ 520,800, an innovative financing solution, was accessed by 334 farmers in one Kenyan county to procure drought-resistant seeds, manage rainwater runoff, and improve soil health. The bundled product integrates bank risk capital, insurance, and climate-smart advisory services. Enabled by CGIAR innovations, 569 farmers were trained, with 334 receiving funding approval. Partners Acre Africa and Shalem Investments will scale to 1,000 farmers by 2026, with a potential reach of 42,500.